Implementasi Aplikasi Mobile Banking Muamalat Din Dalam Menilai Kinerja Perbankan Menggunakan Pendekatan Balanced Scorecard - Daingtaw, Nurjana Putri; Zukkifli Bokiu, Niswatin Niswatin, (Pascasarjana STIE Amkop Makassar, 2025)
The implementation of the Muamalat DIN Mobile Banking application in assessing banking performance using the balanced scorecard approach. Thesis of the S1 Accounting Study Program, Department of Accounting, Faculty of Economics, Gorontalo State University. Under the guidance of Mrs. Dr. Niswatin, S.Pd, SE, MSA as supervisor 1 and Mr. Zulkifli Bokiu, SE. Ak, M.Si as supervisor II.This study aims to find out how Bank Muamalat KCP Limboto performs by measuring using the Balanced Scorecard approach which has four perspectives, namely financial perspective, customer perspective, internal business perspective and learning and growth perspective. This study uses a Quantitative method. The data source used in this research is using primary data. This study used questionnaires distributed to customers and employees in sampling. The results of this study show that the performance of Bank Muamalat KCP Limboto is very good, this is shown by the results of the analysis of each perspective. The financial perspective shows an increase from year to year, the customer perspective refers to customer satisfaction with the mobile banking application, the internal business perspective and the growth and learning perspective also shows good results in the process of innovation, operations and services for employees Kata Kunci: Muamalat DIN, Bank Muamalat and Balanced Scorecard